Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Pengungkapan Corporate Social Responsibility - Subadriyah Subadriyah; Zihanna Syafinatun Nayyiroh (Indonesian Accounting Literacy Journal, 2021)
Abstract: The purpose of this research is to analyze the influence of size, profitability, leverage, on the disclosure of social responsibility in the annual report. Scope of this research is descriptive quantitative with the research object of manufacturing companies in the basic industry and chemical sectors listed on the Indonesia Stock Exchange for the period 2017-2019. This research is a quantitative research with multiple linear regression analysis. The data used are secondary data in the form of corporate financial reports for 2017 to 2019. The population used in this study is all 68 companies in the basic industry and chemical sector in the Indonesia Stock Exchange and a sample of 13 companies was obtained. The results of this study indicate that size has a significant positive effect on CSR disclosure, profitability has a negative effect on CSR disclosure, and leverage has a significant negative effect on CSR disclosure. Keywords: Size, Leverage, Profitability, CSR Disclosure.